2022
DOI: 10.1126/sciadv.abn9683
|View full text |Cite
|
Sign up to set email alerts
|

Using satellites to uncover large methane emissions from landfills

Abstract: As atmospheric methane concentrations increase at record pace, it is critical to identify individual emission sources with high potential for mitigation. Here, we leverage the synergy between satellite instruments with different spatiotemporal coverage and resolution to detect and quantify emissions from individual landfills. We use the global surveying Tropospheric Monitoring Instrument (TROPOMI) to identify large emission hot spots and then zoom in with high-resolution target-mode observations from the GHGSa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
80
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 97 publications
(82 citation statements)
references
References 49 publications
1
80
1
Order By: Relevance
“…However, few studies in China and worldwide have performed atmospheric inversions for city-scale waste treatment especially by using tower-based observations, which can present an independent evaluation method. the EDGAR inventory, where emissions from landfills accounted for 6~50% of total emissions (Maasakkers et al, 2022). In our study, we found that the annual waste A few observation-based measurements have been conducted for waste treatment but only at specific sites with large discrepancies in EFs (Du et al, 2017;Cai et al, 2018;NBSC, 2015;Wang et al, 2015;Florentino et al, 2010;Tolaymat et al, 2010;Cai et al, 2014;.…”
Section: Discussionmentioning
confidence: 55%
See 2 more Smart Citations
“…However, few studies in China and worldwide have performed atmospheric inversions for city-scale waste treatment especially by using tower-based observations, which can present an independent evaluation method. the EDGAR inventory, where emissions from landfills accounted for 6~50% of total emissions (Maasakkers et al, 2022). In our study, we found that the annual waste A few observation-based measurements have been conducted for waste treatment but only at specific sites with large discrepancies in EFs (Du et al, 2017;Cai et al, 2018;NBSC, 2015;Wang et al, 2015;Florentino et al, 2010;Tolaymat et al, 2010;Cai et al, 2014;.…”
Section: Discussionmentioning
confidence: 55%
“…Although some progress has been made in measuring site-scale CH4 emissions from waste treatment, the estimated emissions still show large discrepancies owing to many factors, such as the amount of waste and its composition, meteorological conditions, such as temperature and water content, proportion between landfills and incineration, degradable organic carbon ratio, CH4 oxidation efficiency, and landfill gas collection (Masuda et al, 2018;Cai et al, 2018;Hua et al, 2022;Bian et al, 2022;Maasakkers et al, 2022). Furthermore, CH4 emissions from sewage and landfills are caused by microbial process, especially methanogens, and their emission factors (EFs) are highly sensitive to temperature.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…dysfunctional natural gas flaring systems (Irakulis-Loitxate et al, 2022a, b;Plant et al, 2022). Super-emitters are not limited to oil and gas production but also occur in the coal mining and waste sectors (Cusworth et al, 2020;Sadavarte et al, 2021;Maasakkers et al, 2022b). Detection, localization, and global monitoring of these methane super-emitters provides a large opportunity to reduce emissions (UNEP and CCAC, 2021;Parry et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Varon et al (2021) demonstrated that the Multi-Spectral Instrument, a band imaging instrument onboard the Sentinel-2 satellite (Drusch et al, 2012), is capable of retrieving large methane plumes with a pixel resolution of 20 m for continuous, 290 km wide swaths over favorable terrain. TROPOMI's daily global coverage is particularly well suited to guide observations of these high-resolution instruments, that often have limited viewing domains, to identify large sources of methane at facility level (Irakulis-Loitxate et al, 2022b;Maasakkers et al, 2022b). TROPOMI has collected over 5 years of methane data, which include numerous methane emission plume signals that cannot feasibly be identified manually.…”
Section: Introductionmentioning
confidence: 99%